2014
DOI: 10.1044/2014_jslhr-l-12-0363
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Performance of Children With Specific Language Impairment and Their Typically Developing Peers on Nonverbal Cognitive Tests: A Meta-Analysis

Abstract: The lower performance of children with SLI relative to TD children on nonverbal IQ tests has theoretical implications for the characterization of SLI and clinical and political implications regarding how nonverbal cognitive tests are used and interpreted for children with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
88
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 186 publications
13
88
0
5
Order By: Relevance
“…The average composite z score for the qualifying measures for the children in the TD group was 0.08 with a SD of 0.60 (range = −0.96 to 1.89), which was significantly larger than that for the SLI group, F(1, 233) = 556.74, p < .0001, η 2 = .71. Although the children in both the TD and SLI groups exhibited normal-range nonverbal IQ, the children in the TD group obtained a significantly higher score than the children in the SLI group, F(1, 233) = 46.22, p < .0001, η 2 = .17, a finding that is consistent across the SLI literature (Gallinat & Spaulding, 2014). Johnston (1982) and Swisher, Plante, and Lowell (1994) suggested that nonverbal IQ scores may not serve as measures of general intelligence in children with language impairment.…”
Section: Td Groupsupporting
confidence: 77%
“…The average composite z score for the qualifying measures for the children in the TD group was 0.08 with a SD of 0.60 (range = −0.96 to 1.89), which was significantly larger than that for the SLI group, F(1, 233) = 556.74, p < .0001, η 2 = .71. Although the children in both the TD and SLI groups exhibited normal-range nonverbal IQ, the children in the TD group obtained a significantly higher score than the children in the SLI group, F(1, 233) = 46.22, p < .0001, η 2 = .17, a finding that is consistent across the SLI literature (Gallinat & Spaulding, 2014). Johnston (1982) and Swisher, Plante, and Lowell (1994) suggested that nonverbal IQ scores may not serve as measures of general intelligence in children with language impairment.…”
Section: Td Groupsupporting
confidence: 77%
“…Although both groups scored within the average range according to the norms of the TONI, there was a statistically significant group difference, F(1, 38) = 8.80, p = .005, h p 2 = .188. This is not an unusual finding: A recent meta-analysis showed that across 131 studies published between 1995 and 2012, children with SLI scored, on average, 0.69 SD below their peers with TLD on measures of nonverbal cognition (Gallinat & Spaulding, 2014).…”
Section: Participantsmentioning
confidence: 94%
“…Given that dyslexia is a brain-based developmental disorder, it is not surprising to find some of these differences. Just as specific language impairment is notoriously nonspecific in terms of deficits (e.g., lower IQ; Gallinat & Spaulding, 2014), it is not surprising to find evidence of other mild cognitive and learning differences in children with dyslexia. However, that does not make it easy to interpret how these differences may play a role in performance on different tasks children with dyslexia encounter daily.…”
Section: Nature Of Learnersmentioning
confidence: 99%